Consumer Preference Towards Fruit Leather Attributes of Madurese Exotic Tropical Fruits - Fauziyah, Elys (International Research Journal of Business Studies, 2017)
Madura island has high potential for producing tropical fruits, but it still not being well managed especially concerning with the value added. Fruit leather is a product created by using various fruits and simple technology application. Fruit leather is categorized as new product on the market, therefore it is important to know consumer preference towards fruit leather attributes so that producer can design an acceptable product in the market. The research investigated attributes within the levels that become consumer preference in purchasing fruit leather product. There were 60 samples respondents taken accidentally at Bangkalan Plaza Shopping area. Method being used was conjoint analysis. Result showed that fruit leather being chosen by consumers as preference are gummy, mixed fruit taste, yellow color, small roll shape, at 100 grams and in a plastic tube package.